Balanced Neutrosophic Graphs - S, Sivasankar; Broumi, Said (Neutrosophic Sets and Systems, 2022)
In this paper, we introduce the concept of balanced neutrosophic graphs based on density functions and investigate some of their properties. The necessary conditions for a neutrosophic graph to be a balanced neutrosophic graph are identified if graph G is a selfcomplementary, regular, complete, and strong neutrosophic graph. Some properties of complement neutrosophic graphs are presented here.